Individuals’ reasons for becoming substance addict according to social perspective: a quantitative study - Erkoç, Beyza; Avçin, Emel; Danış, Mehmet Zafer (Journal of Dependence, 2021)
Objective: This study aimed to determine the reasons for individuals to be addicted to substances based on the social perspective and to reveal whether the results vary according to demographic characteristics. Method: The study data were obtained from 416 individuals between 18 and 65 who lived in Yalova between 01.10.2020 and 30.11.2020. Data were collected with the support of researchers and pollsters. Results: The 3- dimensions construct validity of the questionnaire form used to determine the perspective of the society on substance addiction was achieved. These dimensions were named as family, socio-cultural environment, and near-distant environment. The final questionnaire form, consisting of 18 questions, is scored between 0 and 5. The scores of the participants from the final questionnaire form: the immediate environment factor (4 questions) score is 13.63±4.77, the family factor (7 questions) score is 24.58±7.21, and the socio-cultural factor (7 questions) score is 24.57±6.66. Conclusion: The three dimensions in the final questionnaire form are significant in terms of individuals being addicted to substances.